Personality characteristics of athletes who are engaged in martial arts - Гант [Olena Gant] Олена Євгенівна; Сігал [Natalia Sigal] Наталля Семенівна; Штих [Viktoria Shtykh] Вікторія Анатолієвна (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Based on a survey of psychodiagnostic 57 athletes combat sportsman 18-24 characterized personality athletes involved aikibudo and taekwondo. Shown that the system of value orientations combat sportsman serves as the foundation of their life strategy. It is established that the representatives of the sport have the positive dynamics of the self-assessment throughout the whole competition activity. The dependence of the degree of personal anxiety and self combat sportsman on the level of their skills and athletic experience. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>